The Association of Fetal and Early Childhood Growth with Adult Mental Distress: Evidence from the Johns Hopkins Collaborative Perinatal Study Birth Cohort - Alford, Aaron A. (Frontiers in Psychiatry, 2013)
Objectives: Early childhood physical growth may have an impact on the development of adult mental distress. The primary objectives were to (1) assess the association of early growth in weight (adjusted for height) with adult mental distress, and (2) determine if specific sub-types, or patterns, of early physical growth are associated with adult mental distress. Methods: Subjects were all Johns Hopkins Collaborative Perinatal Study cohort subjects with complete birth size information that successfully completed the Pathways to Adulthood follow-up in early adulthood. Variability in the timing of growth in weight adjusted for height from birth to age 7.5 years was taken into account using a nonhierarchical linear model. Two critical periods of growth were considered as tertiles of change in weight adjusted for height from birth to age seven and birth to age 1 year. Mental distress in adulthood (ages 29-32) was measured using the General Health Questionnaire (GHQ-28). Results: Small for gestational age subjects were at increased risk of later mental distress, but not uniformly so. Those born with low weight and length for gestational age were a distinct subgroup of those born small for gestational age, and had unique patterns of risk for adult mental distress when early growth was considered. Conclusions: Acceleration and deceleration in weight for height change is associated with mental distress over multiple periods of early life and acts differentially between those periods. Furthermore, the association of early childhood growth with the likelihood of adult mental distress is dependent on prenatal growth.